PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CV. DAENG KULINER MAKASSAR - Kahar; Mukhtar Tompo (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2025)
The purpose of this study was to determine how much influence service quality has on consumer satisfaction at CV. Makassar Culinary Daeng. This Research Method Refers To The Quantitative Method This Is Because In The Decision Making Process Based On The Results Of Statistical Tests. The Data From This Research Are Taken From 90 Respondents Who Are Consumers On Cv. Culinary Daeng Makassar City. The Data Analysis Techniques Used Are Based On Statistical Tests Regulated With Field Observations. The results of this study indicate that the service quality variable has a positive effect on consumer satisfaction at Cv. Culinary Daeng Makassar City. The author also provides suggestions for further research to provide more in-depth variables regarding consumer satisfaction issues.